Emergent Omicron BR.2.1 sublineage of SARS-CoV-2 in New South Wales, Australia: a subvariant with high fitness but without increased disease severity. (May 2023) - Howard-Jones, Annaleise R; Arnott, Alicia; Draper, Jenny; Gall, Mailie; Ellis, Sally; Marris, Kelsi; Selvey, Christine; Basile, Kerri; Dwyer, Dominic E; Sintchenko, Vitali; Kok, Jen
Highlights: BR.2.1 emerged locally within New South Wales, Australia, in September 2022. By late November 2022, BR-2 became the predominant SARS-CoV-2 variant in New South Wales. BR.2.1 causes SARS-CoV-2 reinfections in the community, but not severe COVID-19. With increased global travel, BR.2.1 has already been detected outside Australia. Abstract: Objectives: To describe the epidemiology and impact of Omicron BR.2.1, an emergent SARS-CoV-2 Omicron BA.2.75 sublineage displaying high fitness compared to other cocirculating subvariants in New South Wales, Australia. Methods: From September 01 to November 26, 2022, 4971 SARS-CoV-2 consensus genomes from unique patients were generated, and correlated with international travel and reinfection history, and admission to the intensive care unit. Results: BR.2.1 became the predominant variant by late November, and was responsible for a significantly higher proportion of community-acquired cases during the study period (55.1% vs 38.4%, P < 0.001). Reinfections (defined as occurring between 6 and 24 weeks after a prior diagnosis of COVID-19) were significantly higher among BR.2.1 compared to non-BR.2.1 infected persons (17.0% vs 6.0%, P < 0.001). BR.2.1 cases were also significantly younger compared to non-BR.2.1 (median age 48 years (interquartile range [IQR] 32) vs 53 years (IQR 32), P  = 0.004). The proportion of patients admitted to the intensive care unit with BR.2.1 was not significantly higher than other subvariants (2.3% vs 2.0%, P  = 0.717). Conclusion: Having emerged locally within New South Wales, BR.2.1 caused a significant number of SARS-CoV-2 reinfections, but with disease severity comparable with other currently circulating lineages. Given its rapid rise in prevalence, BR.2.1 has the potential to become established internationally.